Pengaruh Free Cash Flow, Total Hutang Dan Laba Bersih Ter-hadap Return Saham Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Nuryani Nuryani; Fajar Aribowo (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2023)
This study aimed to examine the significant effect of free cash flow, total debt and net income on stock returns. The variables used are free cash flow, total debt, and net income as the independent variables and stock returns as the dependent variable.Researchers took samples of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2018 – 2021. Sampling used a purposive sampling method. Of the 51 registered companies that became the population in this study, only 17 companies met the criteria. The t-test results showed that free cash flow significantly affected stock returns, total debt had no significant impact on stock returns, and net income significantly affected stock returns. Free cash flow, total debt and net income simultaneously considerably affect stock returns. The test results of the coefficient of determination show that the magnitude of the influence of free cash flow, total debt and net income on stock returns is 54.4%. In comparison, other variables influence the remaining 45.6%.